Measurement of wettability and surface roughness for metrology and quality control in microfluidics - Daugbjerg Thomas Schrøder; Crouzier Loïc; Delvallée Alexandra; Ogheard Florestan; Pecnik Christina; Romieu Kevin; Saraiva Fernanda; Batista Elsa (International Journal of Metrology and Quality Engineering)
Microfluidics is a rapidly growing technology with applications in biochemistry and life sciences. To support the ongoing growth there is a need for common metrology, quality control, and standardisation. Here measurements of wettability and surface roughness can contribute, and these quantities affect flow characteristics of devices, bonding processes in manufacturing, and special microfluidic mechanisms such as droplet formation and spreading of fluids on surfaces. To quantify wettability, an optical laboratory setup was used to measure liquid drop contact angles of three liquids on a microfluidic surface. To further quantify wettability, the Owens, Wendt, Rabel, and Kaelble model was applied to contact angle measurements to determine the total surface free energy. To quantify surface roughness, atomic force microscopy and stylus profilometry measured area roughness parameter and profile roughness parameter for four samples of microfluidic surfaces. The wettability methods successfully demonstrated measurements of contact angles, and these methods were applied to determine a value for the total surface free energy. AFM and stylus profilometry successfully determined surface roughness parameters, and the determined values agreed with the expected for the material. In conclusion, the demonstrated methods can contribute to metrology, quality control and standardisation in microfluidics.